The DANIsh VASculitis cohort study: protocol for a national multicenter prospective study including incident and prevalent patients with giant cell arteritis and polymyalgia rheumatica - Nielsen, Berit D.; Kristensen, Salome; Donskov, Agnete; Terslev, Lene; Dreyer, Lene Wohlfahrt; Colic, Ada; Hetland, Merete Lund; Højgaard, Pil; Ellingsen, Torkell; Hauge, Ellen-Margrethe; Chrysidis, Stavros; Keller, Kresten K. (Frontiers in Medicine, 2024)
The DANIsh VASculitis cohort study, DANIVAS, is an observational national multicenter study with the overall aim to prospectively and protocolised collect clinical data and biobank material from patients with polymyalgia rheumatica (PMR) and giant cell arteritis (GCA) diagnosed and/or followed at Danish rheumatology departments. A long-term key objective is to investigate whether the use of new clinically implemented diagnostic imaging modalities facilitates disease stratification in the GCA-PMR disease spectrum. In particular, we aim to evaluate treatment requirements in GCA patients with and without large vessel involvement, treatment needs in PMR patients with and without subclinical giant cell arteritis and the prognostic role of imaging in regard to aneurism development. Hence imaging stratification is hypothesized to be able to guide management strategies in GCA and PMR. With an established infrastructure within rheumatology for clinical studies in Denmark, the infrastructure of the Danish Rheumatologic Biobank and possibility to cross-link data with valid nation-wide registries, the DANIVAS project holds an exceptional possibility to collect comprehensive real-world data on diagnosis, disease severity, disease duration, treatment effect, complications and adverse events. In this paper, we present the research protocol for the DANIVAS study. Ethics and dissemination: Ethics approval has been obtained (reference number 1-10-72-174-22). Results of the study will be submitted for publication in peer-reviewed journals. Registration details: Clinical trial registration number NCT05935709